Equity and Quality Dimensions in Educational Effectiveness - Kyriakides, Leonidas (Policy Implications of Research in Education,, 2018)
This book aims to make a contribution to the theory, research and practice on quality and equity in education by providing a comprehensive overview of these two dimensions of educational effectiveness and proposing a methodological instrument that may be used to measure the contribution that each school can make to promoting equity. The importance of using this instrument is demonstrated by analysing results of various effectiveness studies conducted over the last decade. The book draws upon research across the world, especially research conducted in the Europe, the United States, and Australasia. It is shown that promoting equity has no negative effect on the promotion of quality. The importance of using this methodological instrument to identify factors that promote both quality and equity at different educational levels (i.e. teacher, school and educational system) is stressed. The book also demonstrates how we can measure stability and changes in the effectiveness status of schools over time in terms of fostering quality and equity. In addition it underlines the importance of identifying factors measuring changes in the effectiveness status of schools in terms of equity and points to the alternative strategies that can be used at school and system level. In our attempt to encourage the further development and use of this methodology for school improvement purposes, we demonstrate how experimental studies can be conducted to discover whether and under which conditions the proposed methodology can help schools promote both quality and equity. Finally, implications for school evaluation, research, educational policy and practice are drawn. In this way, the book contributes significantly to the debate on how quality and equity can be achieved and encourages policy-makers and practitioners not to view these two dimensions of effectiveness as being in competition with each other but as constituting the major objectives of any reform policy and/or improvement effort at school and/or national levels.